Grammar in the composition classroom - Reid, Joy M. (Newbury House teacher development., 1998)
Grammar in the Composition Classroom is designed to allows teachers to write essays on selected topics. The ultimate result is to provide readers with a combination of theoretical and practical information that can be used to motivate and guide curriculum and materials design projects.